HIV/AIDS amongst street children in Cameroon: their relative knowledge, attitudes and sexual experience - Cumber, Samuel Nambile; Tsoka-Gwegweni, Joyce Mahlako; Jackson Jr, Ndenkeh N.; Kanjo-Cumber, Rosaline Yumumkah (International Journal Of Community Medicine And Public Health, 2017)
Background: Street children are victims of society and are up to 10 - 25 times more vulnerable and affected by HIV/AIDS than their counterparts who live with their families. Objective of study: To examine the HIV/AIDS-related knowledge, attitudes and sexual experience amongst street children in Cameroon. Methods: This study was an analytical cross-sectional survey conducted during the year 2015 through the administration of questionnaires to 399 street children that had been homeless for at least a month. Results: Out of the 399 participants interviewed, more than 90% of them reported to have heard about HIV/AIDS. Though only 14% of the participants knew about the importance of HIV screening, an even smaller proportion of about 6.02% of them reported having been HIV screened before. Most of them stated that HIV could be transmitted through kissing, mosquito bites, eating utensils and through a hand-shake as well as believed that screening and use of Voluntary Confidentiality Counseling and Testing (VCCT) could help prevent its transmission. Many of them also thought of HIV/AIDS as a punishment from God for sins or as witchcraft; and that the disease could be cured through believing in God or even by a traditional practitioner. Conclusions: The level of HIV/AIDS knowledge among street children in the study setting is sub-optimal. Their negative attitudes and incorrect beliefs about the disease could make them even more vulnerable to HIV infection. The use of peer educators would be an effective strategy to implement among this hard to reach population